IMPLEMENTATION OF ARTICLE 3 LAW NUMBER 4 OF 2009 CONCERNING MINERAL AND COAL MINING IN THE GRANTING OF EXPLORATION MINING BUSINESS LICENSE - Anggalana; Dery Putra; Chandra Reformasi (PRANATA HUKUM, 2021)
Indonesia is a country rich in natural resources. Therefore, the Government isexpected to be able to manage these natural resources with the aim of people's welfare in accordance with the mandate of the Constitution of the Republic of Indonesia 1945 as stipulated in Article 33 paragraph (3) which reads "The Earth, water and natural resources contained therein are controlled by the state and used for the greater prosperity of the people ". Article 3 of Law Number 4 Year 2009 concerning Mineral and Coal Mining provides guidelines for the government in the implementation of mining business activities and to support the implementation of licensing of mining business activities. The issue of how to implement the granting of exploration mining business licenses based on Article 3 of Law No. 4 of 2009 on Mineral and Coal Mining in Lampung Province and how to supervise mining business activities in Lampung Province. The method used uses normative and empirical juridical research. The implementation of the granting of exploration mining business licenses based on Article 3 of Law No. 4 of 2009 on Mineral and Coal Mining in Lampung Province has been running but not yet maximal because the permit process is too long so that the purpose of the implementation of mining business activities is not achieved. The suggestion is that the license for exploration mining activities must be carried out by one government agency / agency, in order to facilitate the process of obtaining the permit in order to support the effectiveness of mining activities and the cycle of domestic mining investment, especially in Lampung Province.